1992
DOI: 10.1128/jb.174.7.2152-2159.1992
|View full text |Cite
|
Sign up to set email alerts
|

KdpD and KdpE, proteins that control expression of the kdpABC operon, are members of the two-component sensor-effector class of regulators

Abstract: The Kdp system of Escherichia coli, a transport ATPase with high affinity for potassium, is expressed when turgor pressure is low. Expression requires KdpD, a 99-kDa membrane protein, and KdpE, a 25-kDa soluble cytoplasmic protein. (16,41,49). We suggest that phosphoKdpE is a positive effector of Kdp expression and that low turgor pressure causes KdpD to phosphorylate KdpE. MATERUILS AND METHODSDNA sequencing. The 1.7-kb EcoRI fragment of kdpD, cut from plasmid pWE1103 (35), and the 3-kb EcoRI-HindIII fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
155
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(156 citation statements)
references
References 45 publications
0
155
0
1
Order By: Relevance
“…We found that the rate of expression of the KdpD protein is dependent on the K' concentration in the growth medium, leading to the detection of phosphorylation of the chromosome-encoded KdpD protein. In addition, we Kollmann and Altendorf, 1993Polarek et al, 1988Klionsky et al, 1984Yanish-Perron et al, 1985Puppe et al, 1992Walderhaug et al, 1992Walderhaug et al, 1992 this study Pharmacia this study Tabor and Richardson, 1985Tabor and Richardson, 1985Messing and Vieira, 1982 this study provide experimental evidence obtained by site-directed mutagenesis that the conserved histidine (His673) may represent the phosphorylation site in KdpD.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…We found that the rate of expression of the KdpD protein is dependent on the K' concentration in the growth medium, leading to the detection of phosphorylation of the chromosome-encoded KdpD protein. In addition, we Kollmann and Altendorf, 1993Polarek et al, 1988Klionsky et al, 1984Yanish-Perron et al, 1985Puppe et al, 1992Walderhaug et al, 1992Walderhaug et al, 1992 this study Pharmacia this study Tabor and Richardson, 1985Tabor and Richardson, 1985Messing and Vieira, 1982 this study provide experimental evidence obtained by site-directed mutagenesis that the conserved histidine (His673) may represent the phosphorylation site in KdpD.…”
mentioning
confidence: 91%
“…In plasmid pPV5, the kdpD gene is under the control of the tuc promoter. Plasmid pPV11, in which the kdpE gene is located downstream of the T7 promoter, was constructed by cloning the I-kb CluI-SmuI fragment of pPV2 (Walderhaug et al, 1992) into plasmid pT7-6 (Tabor and Richardson, 1985) digested with SmuI. Prior to that, the CluI ends of the 1-kb fragment had been filled-in using the Klenow fragment of DNA polymerase I of E. coli.…”
Section: Bacterial Strains Plasmids and Growth Conditionsmentioning
confidence: 99%
“…The kdpD gene has been cloned, sequenced, and overexpressed (12). The gene product KdpD is an integral protein of the cytoplasmic membrane (13).…”
mentioning
confidence: 99%
“…(17), and pPV5-1 (21) were used. Plasmid pPV5-1 is a derivative of plasmid pPV5 (12), which contains five unique restriction sites that were introduced by silent mutation (21). All these plasmids are derivatives of pKK223-3, in which kdpD is under the control of the tac promoter.…”
mentioning
confidence: 99%
“…Plasmid pBD/H673Q encodes the KdpD derivative with the inactivated phosphorylation site (KdpD/H673Q) (5). In plasmid pPV2, the kdpDE operon is under control of the lac promoter (1). Plasmids pPV2/1-395 and pPV2/1-395/D52N were obtained by digestion of plasmid pPV5-3/1-395 (11) with restriction enzymes NsiI and StuI, and the purified fragment was then ligated to similarly treated vector pPV2 or pPV2/D52N (see below), respectively.…”
Section: Materials-[␥-mentioning
confidence: 99%